PENGARUH SELF ASSESSMENT SYSTEM, PEMERIKSAAN PAJAK, DAN PENAGIHAN PAJAK TERHADAP PENERIMAAN PAJAK PERTAMBAHAN NILAI (PPN) PADA KPP PRATAMA PALEMBANG ILIR TIMUR - Jennie Marcella Chandra; Desitama Anggraini, Leriza; Meiriasari, Vhika (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
The study aims to analyze, find out and prove whether there is an effect of Self assessment system, Tax Audit and Tax Collection on Value Added Tax (VAT) Revenue at KPP Pratama Palembang Ilir Timur. The sampling method is an incidental method. The determination of the sample was determined using the Slovin formula, which was as many as 100 people. Data analysis using SPSS 25. The results of the study are that there is a significant influence of the Self assessment system, Tax Audit, and Tax Collection on VAT Revenue at KPP Pratama Palembang Ilir Timur with a sig f value of 0.000 < α (0.05). There is a significant influence of the Self assessment system on VAT Revenue at KPP Pratama with a sig t value of 0.000 < α (0.05). There is a significant effect of Tax Audit on VAT Revenue at KPP Pratama with a sig t value of 0.001 < α (0.05). There is a significant effect of Tax Collection on VAT Revenue at KPP Pratama with a sig t value of 0.048 < α (0.05).